Pengembangan e-modul berbasis flip builder pada pokok bahasan larutan elektrolit dan non elektrolit kelas X - Lidya Kristina Tualena; Yunita Pare Rombe; Murtihapsari Murtihapsari (Universitas Sebelas Maret, 2024)
Tujuan dari penelitian ini adalah menganalisis tingkat kevalidan, kepraktisan, dan respon siswa terhadap penggunaan E-Modul larutan elektrolit dan non-elektrolit yang dikembangkan dengan aplikasi Flip Builder. Metode penelitian adalah Research & Development (R&D) pendekatan model ADDIE, yang mencakup lima tahapan: Analysis, Design, Develop, Implementation, dan Evaluation. Teknik analisis data yaitu observasi, wawancara, lembar validasi, dan angket yang diisi oleh peserta didik. Berdasarkan penelitian diperoleh hasil bahwa E-Modul yang dikembangkan memiliki tingkat validitas sebesar 91.96%. Hasil angket respon siswa tingkat kepraktisan diperoleh hasil sebesar 76.10% sehingga E-Modul larutan elektrolit dan Non Elektrolit valid dan praktis. Sehingga aktivitas dalam belajar mengajar dapat lebih jelas, efektif, efesien dan interaktif dalam mencapai tujuan pembelajaran. Development of e-modules based on flip builder on the subject of electrolyte and non-electrolyte solutions class X Abstract: This study aims to find out how to develop and determine the level of validity and practicality of the flip builder-based E-Module, as well as to find out the students' responses to the E-Module developed. This research method is Research & Development (R&D) using the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection tools in this study are observation, interviews, validation sheets, and student questionnaire sheets. Based on the results of the study the E-Module developed through the analysis stage (problem determination analysis and needs analysis), the design stage (designing the needs, objectives, content, and structure, visual design of the E-Module), the development stage (developing, and validating the E-Module in accordance with the suggestions of the validator) implementation (conducting trials of products that have been developed) and evaluation (E-Module in the final revision evaluation of the developed product). The research results from the assessment of the E-Modul validator developed have a validity level of 91.96%. Based on the results of the student response questionnaire, the practicality level was 76.10% so the electrolyte and non-electrolyte solution E-Modules were valid and practical to use.